2017
DOI: 10.3329/dujps.v16i1.33376
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Solvation Free Energy, Dipole Moment, Polarizability, Hyperpolarizability and Molecular Properties of Betulin, a Constituent of Corypha taliera (Roxb.)

Abstract: Ab initio calculations were carried out to studysolvation free energy, dipole moment, molecular electrostatic potential (MESP), Mulliken charge distribution, polarizability, hyperpolarizability and different molecular properties like global reactivity descriptors (chemical hardness, softness, chemical potential, electronegativity, electrophilicity index) of betulin. B3LYP/6-31G(d,p) level of theory was used to optimize the structure both in gas phase and in solution. The solvation free energy, dipole moment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…The result showed that the magnitude (from − 8.03 to + 8.03 a.u.) of the total atomic dipole moment |μ (D) | was the largest for the BNA + 5CB complexes, indicating that it exhibited the highest interaction energy (E int ) 65,66 . Consequently, BNA doping increased E int and the dipole moment (μ) and significantly increased the permittivity of the LC mixture 67 , as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that the magnitude (from − 8.03 to + 8.03 a.u.) of the total atomic dipole moment |μ (D) | was the largest for the BNA + 5CB complexes, indicating that it exhibited the highest interaction energy (E int ) 65,66 . Consequently, BNA doping increased E int and the dipole moment (μ) and significantly increased the permittivity of the LC mixture 67 , as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They have been used for the classification of molecules as either electron-donors or electron-receptors. Molecules with larger values   are categorized as better electron acceptors and those with smaller values of   considered as better electron-donors [24]. The values of these properties were calculated using the equations below and presented in Table 6.…”
Section: Electro-donating Power (  ) Electroaccepting Power (   ) and Net Electrophilicity (   )mentioning
confidence: 99%
“…Electrophilicity index () refers to the measurement of energy decrease because of maximal electron flow between donor and acceptor. Global electrophilicity index () is predicted by employing electronegativity and chemical hardness parameters in the equation [16,13].…”
Section: Table 1 Chemical Parameters For Iomeperolmentioning
confidence: 99%